2004
DOI: 10.1080/13550280490448043
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of both endoplasmic reticulum– and mitochondria-dependent pathways in MoMuLV-ts1–induced apoptosis in astrocytes

Abstract: The Moloney murine leukemia virus (MoMuLV)-ts1 retrovirus, a naturally occurring mutant of MoMuLV-TB, causes a neuroimmunodegenerative syndrome in mice. The authors show here that ts1 triggers apoptosis in immortalized astrocytes, C1 cells, and primary cultured astrocytes, and that this apoptosis is caused by endoplasmic reticulum (ER) stress resulting from accumulation of the viral envelope preprotein gPr80(env). In ts1-infected C1 cells, an unfolded protein response was identified by activation of the ER-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 52 publications
6
46
0
Order By: Relevance
“…22,38 Here, we have shown that levels of ER stress markers, GRP78 and cleavage of procaspase-12 were also increased in Atm À/À astrocytes (Figure 3a).…”
Section: Atm-deficient Astrocytes Show Signs Of Oxidative Stress and mentioning
confidence: 88%
See 1 more Smart Citation
“…22,38 Here, we have shown that levels of ER stress markers, GRP78 and cleavage of procaspase-12 were also increased in Atm À/À astrocytes (Figure 3a).…”
Section: Atm-deficient Astrocytes Show Signs Of Oxidative Stress and mentioning
confidence: 88%
“…[14][15][16][17] Loss of astrocytic antioxidant support may contribute to neuronal death. [18][19][20][21][22][23] The findings of one study suggest that Atm À/À astrocytes are unable to protect Purkinje cells against oxidative stress. 9 However, it is not clear how Atm À/À astrocytes fail to protect these neurons.…”
mentioning
confidence: 99%
“…As pointed out by Adams (2003) in their review, apoptosis can be simultaneously mediated by two or more signal pathways, but their relative importance is different in response to specific stimuli. For instance, many cell types such as astrocytes (Liu et al 2004), mouse embryonic fibroblasts (Masud et al 2007;Sanges and Marigo 2006), Hela cells (Xu et al 2006), and human teratoma cells (Ferreiro et al 2008) undergo apoptosis through both mitochondrial and ER pathway, and there is evidence showing that both death receptor and mitochondrial pathway simultaneously contribute to disc cell apoptosis (Park et al 2005). We thus hypothesize that mitochondria and the ER might also be co-involved in disc cell apoptosis and therefore play a role in IVDD.…”
Section: Introductionmentioning
confidence: 93%
“…In the course of virus productive infection, a large amount of viral proteins is synthesized in infected cells, where unfolded or misfolded proteins result in ER stress (23). The accumulation of viral envelope proteins in the ER has been implicated as the trigger of the UPR in several virus infections (6,7,12,52,84). For HBV, there are three envelopment proteins.…”
Section: Discussionmentioning
confidence: 99%